Odpowiedzi

2009-11-25T19:22:41+01:00
Najlepsza Odpowiedź!
2009-11-25T19:24:20+01:00
(-3,4) razy 6,1 +(-3,4) razy 3,9 = -3, 4 razy (6, 1 + 3, 9) = - 34


(-2)razy 5,1 + (-2) razy 3,4 +(-2) razy 4,7 = -2 razy (5,1 +3,4 + 4, 7) = -2 razy 13,2 = -26,4


6,4 razy (-4,5) +6,4 razy(-3) -6,4 razy 3 = 6,4 razy [(-4,5) + (-3) - 3] = 6,4 razy (-10, 5 ) = -67, 2


(-5,2)razy (-1,8)+(-1,8) razy 3,7 - (1,8)razy(-5,2) = 1, 8 razy [(-5, 2) +3, 7 + (-5,2)] = 1, 8 razy 6, 7 = 12,06

Mam nadzieje że pomogłam ;)
1 5 1